2015
DOI: 10.5430/jst.v5n2p27
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic adamantinoma responds to treatment with receptor tyrosine kinase and Aurora A kinase inhibitor

Abstract: Adamantinoma is to be known as the one of the least common low-grade malignant bone tumors, commonly arising in the center of long bones, mostly in the tibial mid shaft. Adamantinomas are usually managed with wide local excision and reconstruction, unless unresectable or locally recurrent. Even though adamantinomas are managed as locally aggressive tumors, they usually recur and metastasize to sites including the lymph nodes, lungs, skeleton, liver and brain. Radiotherapy and chemotherapy do not seem to be eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…1,2,4 Targeted therapy with tyrosine kinase inhibitors, such as sunitinib and pazopanib, has been utilized with some durable responses. [14][15][16][17] Sequencing data may improve therapy options, and our patient did have a somatic NF1 mutation and gene rearrangement. Unfortunately, our patient did not respond to chemotherapy or targeted therapy, including trametinib.…”
Section: A Case Of Progressive Metastatic Adamantinoma In a Pediatric Patientmentioning
confidence: 79%
“…1,2,4 Targeted therapy with tyrosine kinase inhibitors, such as sunitinib and pazopanib, has been utilized with some durable responses. [14][15][16][17] Sequencing data may improve therapy options, and our patient did have a somatic NF1 mutation and gene rearrangement. Unfortunately, our patient did not respond to chemotherapy or targeted therapy, including trametinib.…”
Section: A Case Of Progressive Metastatic Adamantinoma In a Pediatric Patientmentioning
confidence: 79%
“…Unal et al recently reported a case of metastatic adamantinoma. They used pazopanib and alisertib (a small molecule Aurora kinase inhibitor) with a good response for 5 months [ 15 ].…”
Section: Discussionmentioning
confidence: 99%